VARIATION IN PHYTOCHEMICAL, PHYSIOCHEMICAL CONTENTS AND TOXICITY OF PRANGOS PLATYCHLAENA BOISS IN HALGURD MOUNTAIN OF IRAQI KURDISTAN - & Jaff, Rahman (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
The wild plant Prangos platychlaena Boiss belonged to the family Apiaceae, is a native plant of Kurdistan-Iraq. The root, leaves, stem and flowers of the plant were collected in the Hlgurd mountain of Kurdistan region of Iraq, and extracted by ethanol solvent to obtain the crude extracts. Our results showed that the phytochemical contents are more concentrated in the initiated growth stage than the other stages and the phytochemical concentration posatively correlated with temperature and negatively correlated with humidity.The physiochemical contents such as total carbohydrate, protein, coumarin and dry weight more concentrated in the leaves and flower than other parts.This experiment was conducted to reveal the toxicity of leaves of the P.platychlaena Boiss on the rat. The results revealed that leaves cause toxicity of rats and its lethal dose was 3.95g/kg this is due to the leaves part containing large amount of coumarin than other aerial parts. These finding sugested that this plant, specially their leaves must not be used as the fooder for animals